The Effect of Psycho-Educational Therapy on Anxiety Levels in Children with Leukemia Undergoing Chemotherapy: A Pre-Experimental Study - Pramadita Elena; Anis Laela Megasari; Ika Subekti Wulandari (Napande: Jurnal Bidan, 2026)
Background: Cancer remains a major global health issue, with approximately 400.000 children and adolescents diagnosed with cancer each year worldwide. Anxiety is one of the most common psychological responses experienced by children undergoing chemotherapy, which may affect treatment cooperation and quality of life. Therefore, this study aimed to analyze the effect of psycho-educational therapy on anxiety levels in children with cancer undergoing chemotherapy. Methods: This study used a pre-experimental study one-group pretest–posttest design conducted at the YKAKI (Yayasan Kasih Anak Kanker Indonesia) in Semarang Halfway House from May to June 2023. A total of 25 children diagnosed with leukemia and undergoing chemotherapy were recruited using total sampling. Data were collected using respondent characteristic observation sheets and the Spence Children’s Anxiety Scale (SCAS) to measure anxiety levels. The psycho-educational therapy consisted of four sessions, including education about cancer and chemotherapy, prevention and management of chemotherapy side effects, and stress management techniques. Data were analysed using the Wilcoxon signed-rank test. Ethical approval was obtained from the Ethics Commission of the Faculty of Medicine, Sultan Agung University. Results: Before the intervention, the majority of respondents experienced severe anxiety (44%). After the intervention, most respondents experienced mild anxiety (72%).  The mean anxiety score decreased from 2.24 ± 0.77 before the intervention to 1.32 ± 0.55 after the intervention, indicating a significant reduction of 0.92 points (41.1%) after the intervention (p = 0.001). Conclusion: This study indicates a potential benefit of psycho-educational therapy in reducing anxiety. This intervention may be considered a supportive psychological strategy to help reduce anxiety in children undergoing chemotherapy.